2005
DOI: 10.1016/j.jacc.2004.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Role of transtelephonic electrocardiographic monitoring in detecting short-term arrhythmia recurrences after radiofrequency ablation in patients with atrial fibrillation

Abstract: Transtelephonic ECG is better than standard ECG and 24-h Holter recordings in evaluating AF relapses after RCA, thus decreasing the short-term success of ablation from 86% to 72%. The absence of symptoms should not be interpreted as absence of AF, as 50% of patients were asymptomatic during at least one AF episode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
1
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(82 citation statements)
references
References 20 publications
4
69
1
8
Order By: Relevance
“…Multiple studies have demonstrated that asymptomatic AF commonly occurs in patients following catheter ablation. 56,57,63,413,442,936,937,938 Detection of these asymptomatic episodes of AF impact the characterization of the procedure as “successful.” Arrhythmia monitoring is an essential component of clinical trials aimed at assessing the outcomes of catheter ablation procedures and should be incorporated into all clinical trials designed to assess the efficacy of AF catheter ablation tools and techniques. The suggested monitoring strategies and minimum standards to be used as part of clinical trials are discussed in Section 13: Clinical Trial Design.…”
Section: Section 8: Follow-up Considerationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Multiple studies have demonstrated that asymptomatic AF commonly occurs in patients following catheter ablation. 56,57,63,413,442,936,937,938 Detection of these asymptomatic episodes of AF impact the characterization of the procedure as “successful.” Arrhythmia monitoring is an essential component of clinical trials aimed at assessing the outcomes of catheter ablation procedures and should be incorporated into all clinical trials designed to assess the efficacy of AF catheter ablation tools and techniques. The suggested monitoring strategies and minimum standards to be used as part of clinical trials are discussed in Section 13: Clinical Trial Design.…”
Section: Section 8: Follow-up Considerationsmentioning
confidence: 99%
“…More intensive monitoring is associated with a greater likelihood of detecting both symptomatic and asymptomatic AF. 57,414, 937,938,939,940,941,942,943,944 The proportion of asymptomatic compared with symptomatic events might be higher after AF ablation; two studies reported that the proportion of AF events that were asymptomatic was 11%–35% prior to and 53%–65% after ablation. 63,945,946 Another study reported that for patients in sinus rhythm, 53.8% of AF episodes were asymptomatic, with an increase in asymptomatic episodes changing from the acute to the chronic period after ablation, demonstrating that AF success cannot be based on the absence of symptoms alone.…”
Section: Section 8: Follow-up Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ablasyon sonrasında ilk 3 aylık dönemde ablate edilen dokuya bağlı ritim düzensizlikleri ve rekürrens görülebildi-ği için antiaritmik tedavi, ablate edilen dokuda sersemlemeye bağlı staz olması ve trombüs için nidus oluşması nedeniyle antikoagülan tedavi önerilmek-tedir. Bu 3 aylık periyoda kör period adı verilmiştir ve ablasyon sonrası rekürrensin bu peryottan sonra değerlendirilmesi önerilmiştir [27][28][29]. Antiaritmikler ablasyonun sebep olduğu inflamasyona bağlı proaritmik etkileri azaltıp erken AF rekürrensini engelleyebilirler.…”
Section: A-v Bloke Edici Ajanlar Ile Ventriküler Hız Kontrolüunclassified